Students’ Acceptance and Perceptions of Tasrif Reverso as a Digital Tool for Sharf Learning: Penerimaan dan Persepsi Mahasiswa terhadap Tasrif Reverso sebagai Media Digital dalam Pembelajaran Sharf - Siti Alfi Aliyah; Muh Fuad Achsan; Miftah Toriqul Ikhwani; Susanti; Rif’atul Fadhilah (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2025)
This study aims to analyze the acceptance and perceptions of students in the Arabic Language Education at Muhammadiyah University of Karanganyar regarding the use of Tasrif Reverso as a digital tool in Arabic language learning, particularly in the sharf course. The research employed a quantitative approach with descriptive analysis techniques. Data were collected through the distribution of questionnaires to PBA students who had taken the sharf course and used the Tasrif Reverso platform during the learning process. A total of 10 questionnaire items were adapted from several journal articles and categorized based on the indicators of the Technology Acceptance Model (TAM), namely External Variable, Perceived Usefulness, Perceived Ease of Use, Attitude Toward Using, and Behavioral Intention. All questionnaire items were analyzed using SPSS through validity and reliability testing. The validity test results indicated that all items were declared valid, with rcalculated values higher than the rtable value (0.532). The reliability test produced a Cronbach’s Alpha value of 0.889, indicating that all items were reliable. The findings of the study show that, in general, students have a positive perception of the use and acceptance of Tasrif Reverso based on the TAM indicators. The platform is considered helpful in understanding the material related to word-pattern changes (tashrif). This research is expected to serve as a reference for the development of digital learning media that can enhance students’ linguistic competence, particularly in the field of Arabic morphology (sharf).